Diagnosis and treatment of patients with gastroesophageal reflux disease - a systematic review of cost-effectiveness and economic burden - Petra Maresova; Lukas Rezny; Jan Hruska; Blanka Klimova; Lee L Swanstrom; Kamil Kuca (BMC, 2024)
Abstract Background This study aims to review the existing knowledge on the cost-effectiveness and item costs related to the diagnosis and treatment of gastroesophageal reflux disease (GERD) patients at different stages. Methods The study adhered to the PRISMA guidelines. The systematic search involved several steps: finding and identifying relevant articles, filtering them according to the set criteria, and examining the final number of selected articles to obtain the primary information. The number of articles published between 2013 and September 2024 in the Web of Science and PubMed databases was considered. The CHEERS checklist was used for the risk of bias assessment. Ultimately, 36 studies were included. Results Regarding the cost-effectiveness of GERD treatment, Proton pump inhibitors (PPIs) appeared to be the dominant solution for non-refractory patients. However, this might change with the adoption of the novel drug vonoprazan, which is more effective and cheaper. With advancements in emerging technologies, new diagnostic and screening approaches such as Endosheath, Cytosponge, and combined multichannel intraluminal impedance and pH monitoring catheters should be considered, with potential implications for optimal GERD management strategies. Discussion The new diagnostic methods are reliable, safe, and more comfortable than standard procedures. PPIs are commonly used as the first line of treatment for GERD. Surgery, such as magnetic sphincter augmentation or laparoscopic fundoplication, is only recommended for patients with treatment-resistant GERD or severe symptoms. Other Advances in emerging technologies for diagnostics and screening may lead to a shift in the entire GERD treatment model, offering less invasive options and potentially improving patients' quality of life.